1996
DOI: 10.1128/mcb.16.12.6810
|View full text |Cite
|
Sign up to set email alerts
|

Spliceosome Activation by PRP2 ATPase prior to the First Transesterification Reaction of Pre-mRNA Splicing

Abstract: In addition to small nuclear RNAs and spliceosomal proteins, ATP hydrolysis is needed for nuclear pre-mRNA splicing. A number of RNA-dependent ATPases which are involved in several distinct ATPdependent steps in splicing have been identified in Saccharomyces cerevisiae and mammals. These so-called DEAD/H ATPases contain conserved RNA helicase motifs, although RNA unwinding activity has not been demonstrated in purified proteins. Here we report the role of one such DEAH protein, PRP2 of S. cerevisiae, in splice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
168
1
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(180 citation statements)
references
References 49 publications
(68 reference statements)
7
168
1
4
Order By: Relevance
“…Other DEAD box proteins could perform functions distinct from RNA unwinding. These possible functions include (1) mediating larger scale RNA structural rearrangements (Figure 10b) (38)(39)(40); (2) altering protein-RNA or protein-protein interactions, analogous to the disruption of protein-DNA contacts in the nucleosome by the Swi/Snf complex ( Figure 10c; the ATPase of the Swi/Snf complex, Swi2/Snf2, is related to the DEAD box family (41,(42)(43)(44)(45)); and (3) functioning, as the G-protein EF-Tu does, as a guarantor of fidelity in RNA-RNA interactions and rearrangements (46). There is no reason to assume a priori that all members of a sequence family of proteins perform the same function.…”
Section: Discussionmentioning
confidence: 99%
“…Other DEAD box proteins could perform functions distinct from RNA unwinding. These possible functions include (1) mediating larger scale RNA structural rearrangements (Figure 10b) (38)(39)(40); (2) altering protein-RNA or protein-protein interactions, analogous to the disruption of protein-DNA contacts in the nucleosome by the Swi/Snf complex ( Figure 10c; the ATPase of the Swi/Snf complex, Swi2/Snf2, is related to the DEAD box family (41,(42)(43)(44)(45)); and (3) functioning, as the G-protein EF-Tu does, as a guarantor of fidelity in RNA-RNA interactions and rearrangements (46). There is no reason to assume a priori that all members of a sequence family of proteins perform the same function.…”
Section: Discussionmentioning
confidence: 99%
“…Prp2, Prp16, and Prp22 associate with the spliceosome at distinct stages and dissociate after they hydrolyze ATP (15,16,32). Their functional specificity is determined at least in part by unique interactions with the spliceosome.…”
Section: Prp43 Functions At a Latementioning
confidence: 99%
“…The samples were incubated on ice for 10 min, and the charcoal was recovered by centrifugation. 32 P radioactivity in the supernatant was quantified by liquid scintillation counting. All the values are averages from at least two reaction mixtures, with a variation of less than 10% between experiments.…”
Section: Expression and Purification Of Recombinant Prp43mentioning
confidence: 99%
“…Splicing of pre-mRNA involves two successive transesterification reactions carried out by a large ribonucleoprotein (RNP) spliceosome complex+ This complex is composed of five snRNAs (U1, U2, U4, U5, and U6) and nearly 100 proteins (Moore et al+, 1993)+ Spliceosome formation involves a complex network of specific and conserved interactions among snRNAs, as well as between snRNAs and pre-mRNA, that lead to formation of the catalytic center+ During this process, an initial interaction of U1 snRNP with the 59 splice site (59SS) is followed by recognition of the branch site by U2 snRNP, yielding splicing complex A+ At the stage of dissociation of the 59SS:U1 snRNA duplex and release of U1 snRNP, U4/U5/U6 tri-snRNP joins complex A to form splicing complex B, which subsequently rearranges into the catalytically active complex C+ Several DExD/ H-box proteins (ATPases/RNA helicases, or unwindases) identified both in yeast and mammalian systems are thought to mediate multiple RNA conformational changes occurring throughout the splicing process (reviewed in Staley & Guthrie, 1998;Murray & Jarrell, 1999)+ One of these factors, yPrp28p, has been implicated in the switch between the initial 59SS:U1 snRNA duplex and the subsequent 59SS:U6 snRNA pairing (Staley & Guthrie, 1998, 1999)+ However, a number of questions concerning the mechanism of action, recognition of RNA substrates, and interactions of these putative RNA helicases with other spliceosomal proteins remain to be answered+ Gorbalenya and Koonin (1993) classified helicases into three major superfamilies based on characteristic motifs shared by these proteins+ Crystal structures of two DNA helicases; PcrA and Rep (Subramanya et al+, 1996;Korolev et al+, 1997;Velankar et al+, 1999), and two RNA helicases; HCV NS3 and eIF4A (Yao et al+, 1997;Kim et al+, 1998), demonstrate that the conserved motifs required for ATP binding and hydrolysis are located at similar positions along the cleft separating two structurally similar protein domains+ Helicases are known to be involved in several biological processes, including replication, translation, transcription, and pre-mRNA splicing (Schmid & Linder, 1992;Lüking et al+, 1998)+ Among the DExD/H-box proteins involved in splicing, several exhibit single-stranded RNAdependent ATPase activity in vitro (Schwer & Guthrie, 1991;Kim & Lin, 1996;O'Day et al+, 1996;Raghunathan & Guthrie, 1998;Schwer & Gross, 1998;Wagner et al+, 1998), but only in a few cases has the ATPdependent RNA unwinding been demonstrated in vitro …”
Section: Introductionmentioning
confidence: 99%